Mapeando fundamentos do Constructo Neuromarketing com profissionais de empresa de publicidade - Soares Neto, João Batista (2007)
This study aims to acknowledge the domain level and influence of the neuromarketing construct. This is done considering professionals at advertising agencies in Brazil. The presence of concepts related to this new approach is very little divulged, and there are little analysis performed on this area. Thus, the research is of qualitative and exploratory nature and used as primary fonts books, articles related to marketing, neuroscience, and psychology as well as secondary fonts. A profound interview was realized aiming the main advertising agencies in Brazil. The public was composed by managers responsible for planning. A content analysis was performed afterwards. The advances related to the brain science have permitted the development of technological innovation. These go primarily towards knowledge and unconscious experiences of consumers, which are responsible for the impulse of decision making and consumer behavior. These issues are related to Neuromarketing, that in turn, uses techniques such as FMRI, PET and FDOT. These scan the consumer s brain and produces imagines on the neuron s structures and functioning. This is seen while activities such as mental tasks for the visualization of brands, images or products, watching videos and commercials are performed. It is observed that the agencies are constantly in search of new technologies and are aware of the limitations of the current research instruments. On the other hand, they are not totally familiar with concepts related to neuromarketing. In relation to the neuroimage techniques it is pointed out by the research that there is full unawareness, but some agencies seem to visualize positive impacts with the use of these techniques for the evaluation of films and in ways that permit to know the consumer better. It is also seen that neuroimage is perceived as a technique amongst others, but its application is not real, there are some barriers in the market and in the agencies itself. These barriers as well as some questioning allied to the scarce knowledge of neuromarketing, make it not possible to be put into practice in the advertising market. It is also observed that even though there is greater use of neuromarketing; there would not be any meaningful changes in functioning and structuring of these agencies. The use of the neuro-image machines should be done in research institutes and centers of big companies. Results show that the level of domain of the neuromarketing construct in the Brazilian advertising agencies is only a theoretical one. Little is known of this subject and the neurological studies and absolutely nothing of neuroimage techniques